Volatile chemical products emerging as largest petrochemical source of urban organic emissions - McDonald, Brian C.; de Gouw, Joost A.; Gilman, Jessica B.; Jathar, Shantanu H.; Akherati, Ali; Cappa, Christopher D.; Jimenez, Jose L.; Lee-Taylor, Julia; Hayes, Patrick L.; McKeen, Stuart A.; Cui, Yu Yan; Kim, Si-Wan; et al. (Science (American Association for the Advancement of Science), 2018)
Transport-derived emissions of volatile organic compounds (VOCs) have decreased owing to stricter controls on air pollution. This means that the relative importance of chemicals in pesticides, coatings, printing inks, adhesives, cleaning agents, and personal care products has increased. McDonald et al. show that these volatile chemical products now contribute fully one-half of emitted VOCs in 33 industrialized cities (see the Perspective by Lewis). Thus, the focus of efforts to mitigate ozone formation and toxic chemical burdens need to be adjusted. Science , this issue p. 760 ; see also p. 744 Chemical products contribute as much organic air pollution as transportation emissions in many cities. A gap in emission inventories of urban volatile organic compound (VOC) sources, which contribute to regional ozone and aerosol burdens, has increased as transportation emissions in the United States and Europe have declined rapidly. A detailed mass balance demonstrates that the use of volatile chemical products (VCPs)—including pesticides, coatings, printing inks, adhesives, cleaning agents, and personal care products—now constitutes half of fossil fuel VOC emissions in industrialized cities. The high fraction of VCP emissions is consistent with observed urban outdoor and indoor air measurements. We show that human exposure to carbonaceous aerosols of fossil origin is transitioning away from transportation-related sources and toward VCPs. Existing U.S. regulations on VCPs emphasize mitigating ozone and air toxics, but they currently exempt many chemicals that lead to secondary organic aerosols.